EU carbon prices signal high policy credibility and farsighted actors - Joanna Sitarz; Michael Pahle; Sebastian Osorio; Gunnar Luderer; Robert Pietzcker (ZBW – Leibniz Information Centre for Economics, 2023)
Carbon prices in the EU emissions trading system (EU ETS) are a key instrument driving Europe's decarbonization. Between 2017 and 2021, they surged tenfold, exceeding 80 exteuro/tCO2 and reshaping investment decisions across the electricity and industry sectors. What has driven this increase is an open question. While it coincided with two significant reforms tightening the cap (“MSR reform” and “Fit for 55”), we argue that a reduced supply of allowances alone cannot fully explain the price rise. A further crucial aspect is that actors must have become more farsighted as the reform signaled policymakers' credible long-term commitment to climate targets. This is consistent with model results that show historic prices can be better explained with myopic actors, while explaining prices after the reforms requires actors to be farsighted. To underline the role of credibility, we test what would happen if a crisis undermines policy credibility such that actors become myopic again, demonstrating that carbon prices could plummet and endanger the energy transition.
Keywords: Q48; Q58; D84; H23; E37; D78; 330; Carbon prices; EU Emissions Trading System (EU ETS); Myopia; Foresight; Market Stability Reserve (MSR); Policy Credibility; European Green Deal; Electricity Decarbonization